Structural characterisation and thermal stability of SnSestacked films. Issue 1 (2nd January 2019) - Sava, F.; Borca, C. N.; Galca, A. C.; Socol, G.; Grolimund, D.; Mihai, C.; Velea, A.
ABSTRACT: We have investigated the effect of thermal annealing on the structure of single and stacked phase change memory films based on SnSe and GaSb. Samples were prepared by pulsed laser deposition and investigated by X-ray absorption spectroscopy (XAS) and X-ray diffraction (XRD) methods. Electrical resistance versus temperature investigations showed crystallisation temperatures of 292°C and 198°C for SnSe and GaSb single films, respectively. Above the transition temperature, GaSb crystallises into a face-centered cubic structure, whereas SnSe has an orthorhombic arrangement. Annealing at three temperatures (160°C, 250°C and 350°C) of the SnSestacked films promotes bond breaking, atom diffusion between the two layers and formation of new phases. At 160°C, GaSb films crystallise partially and no effect is observed on the crystallinity of SnSe films. After 250°C, rhombohedral SnSb emerges in addition to GaSb complete crystallisation. A major, completely new, body-centered orthorhombic unindexed quaternary Ga-Sn-Sb-Se phase formation was observed in the samples annealed at 350°C. The GaSb crystallites are fully dissolved and we have observed the formation of a minor hexagonal SnSe2 phase. The analysis of EXAFS data, measured at Se and Ga K-edges, revealed changes in the local atomic environment as a function of the annealing temperature. A tetrahedral configuration is obtained for the Ga atoms in both as-deposited and annealed samples, whereas Se is mostly bivalent in the amorphous samples and has an octahedral arrangement in crystalline SnSe. Our results show that inter-layer diffusion should always be considered and evaluated when designing memory cells composed of stacked phase change chalcogenide films.